A novel two-step fall detection method using smartphone sensors - Dogan, John C.; Hossain, Md Shafaeat (2019 IEEE International Conference on Smart Computing (SMARTCOMP), 2019)
A smartphone-based fall detection system has two major advantages over a traditional fall detection system that comes as a separate device: (1) the phone can automatically send messages to or call the emergency contact person when a fall is detected and (2) a user does not need to carry an extra device. This paper presents a novel two-step fall detection method which uses data extracted from smartphone sensors to detect falls. A fall can happen in many ways. A person can fall while he/she is walking, jogging, sitting, or even sleeping. Patterns of all falls are not the same. It is important to identify the type of falls to precisely distinguish it from non-falls (normal activities). Hence, our method first identifies the correct type of falls by performing multi-class classification. In the second step, this method produces a binary decision based on the multiclass prediction. We collected data from 10 users to evaluate our proposed fall detection method. Each user performed five normal activities-namely, walking, jogging, standing, sitting, lying, and also fell after performing each activity. We performed experiments with five common smartphone sensors: accelerometer, gyroscope, magnetometer, gravity, and linear acceleration. We tested five machine learning classifiers-namely, Support Vector Machine, K-Nearest Neighbor, Decision Tree, Random Forest, and Naive Bayes. Our two-step fall detection method achieved the maximum accuracy of 95.65% and the maximum area under ROC curve (AUC) of 0.93, both with the gyroscope sensor and Support Vector Machine classifier.
Keywords: Accelerometer; Accelerometers; Activity recognition; Area under roc curve (AUC); Classifiers; Decision trees; Fall detection; Feature extraction; Gyroscope; Gyroscopes; K-nearest neighbors; Legged locomotion; Linear accelerations; Machine learning; Multi-class classification; Multiclass prediction; Nearest neighbor search; Sensor; Sensors; Smartphone; Smartphones; Support vector machine classifiers; Support vector machines; Training; Walking aids; accelerometer; accelerometers; decision tree; decision trees; dept.csc; geriatrics; gravity; gyroscope; gyroscopes; jogging activity; k-nearest neighbor; learning (artificial intelligence); linear acceleration; lying activity; magnetometer; medical computing; naive Bayes; random forest; sitting activity; smart phones; smartphone sensors; smartphone-based fall detection system; standing activity; support vector machine; support vector machines; two-step fall detection method; walking activity

Movement pattern based authentication for smart mobile devices - Rahman, Khandaker Abir; Tubbs, Dustyn J.; Hossain, Md Shafaeat (2018 17th IEEE International Conference on Machine Learning and Applications (ICMLA), 2018)
We outline a novel method of user authentication for smart mobile devices, such as smartphones or tablets and propose movement pattern based authentication as an alternate to current methods that relies on a pin or drawn-pattern. While the current methods are vulnerable against common attacks (e.g., smudge attacks, shoulder surfing), our method, in contrast, is more resilient against the attacks of these kinds because it utilizes sensory data given off by the device during a preset movement for authentication. In our experiment, we recorded the values given off by four physical observational sensors: (1) accelerometer, (2) linear accelerometer, (3) gyroscope and (4) tilt sensor, which each had three axes, over a set of movements. We experimented with 10 arbitrary movement-patterns and gathered 12 samples of each (net 120 samples) to test with. We developed our own method of authentication, through which we performed 35,650 authentication attempts and found a 20.36% Equal Error Rate.
Keywords: Accelerometers; Authentication; Equal error rate; Gyroscopes; Linear accelerometers; Machine learning; Mobile computing; Mobile device; Movement pattern; Screen unlock; Sensory data; Shoulder surfing; Smart phones; Three axes; Tilt sensor; Training; User authentication; accelerometers; authentication; authorisation; dept.csc; gyroscope; gyroscopes; linear accelerometer; message authentication; mobile computing; mobile device; movement pattern; movement pattern based authentication; movement pattern, authentication, screen unlock, mobile device; physical observational sensors; preset movement; screen unlock; smart mobile devices; smart phones; smudge attacks; tilt sensor; user authentication

Sentiment analysis of the correlation between regular tweets and retweets - Chen, Jundong; Li, He; Wu, Zeju; Hossain, Md Shafaeat (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, we study the influence from the sentiment of regular tweets on retweeting. We propose a method to calculate the sentiment score for each tweet and each Twitter user. This method enables us to place the tweets and retweets into the same time period to explore the sentiment factor. We adopt the correlation coefficient between the sentiment scores of regular tweets and those of retweets to measure the influence. We categorize the Twitter users in three different ways to investigate three factors, which are the number of followers, betweenness centrality and the types of accounts. Community detection and machine learning are integrated into our approach. We find that the difference for correlation coefficients exists between different levels of the number of followers, and different types of users. Our method sheds a light on better predicting the dynamics of tweets diffusion by including the sentiment factor into the prediction model. © 2017 IEEE.
Keywords: Artificial intelligence; Betweenness centrality; Community detection; Correlation coefficient; Data mining; Learning systems; Prediction model; Sentiment analysis; Sentiment scores; Social networking (online); Time-periods; Twitter classification; dept.csc; machine learning; sentiment analysis; social network

An empirical study on verifier order selection in serial fusion based multi-biometric verification system - Hossain, Md Shafaeat; Rahman, Khandaker Abir (Springer International Publishing, 2017)
Selecting the order of verifier in a serial fusion based multi-biometric system is a crucial parameter to fix because of its high impact on verification errors. A wrong choice of verifier order might lead to tremendous user inconvenience by denying a large number of genuine users and might cause severe security breach by accepting impostors frequently. Unfortunately, this design issue has been poorly investigated in multi-biometric literature. In this paper, we address this design issue by performing experiments using three different serial fusion based multi-biometric verification schemes, in particular (1) symmetric scheme, (2) SPRT-based scheme, and (3) Marcialis et al.’s scheme. We experimented on publicly available NIST-BSSR1 multi-modal database. We tested 24 orders—all possible orders originated from four individual verifiers—on a four-stage biometric verification system. Our experimental results show that the verifier order “best-to-worst”, where the best performing individual verifier is placed in the first stage, the next best performing individual verifier is placed in the second stage, and so on, is the top performing order for all three serial fusion schemes mentioned above.
Keywords: Biometric verification; Biometrics; Crucial parameters; Intelligent systems; Multi biometrics; Multi-biometric verification; Multibiometric systems; Multimodal database; Order selection; Security breaches; Serial fusion; Verifier order selection; dept.csc

A game theoretic analysis of the twitter follow-unfollow mechanism - Chen, Jundong; Hossain, Md Shafaeat; Brust, Matthias R.; Johnson, Naomi (Springer International Publishing, 2018)
Twitter users often crave more followers to increase their social popularity. While a variety of factors have been shown to attract the followers, very little work has been done to analyze the mechanism how Twitter users follow or unfollow each other. In this paper, we apply game theory to modeling the follow-unfollow mechanism on Twitter. We first present a two-player game which is based on the Prisoner’s Dilemma, and subsequently evaluate the payoffs when the two players adopt different strategies. To allow two players to play multiple rounds of the game, we propose a multi-stage game model. We design a Twitter bot analyzer which follows or unfollows other Twitter users by adopting the strategies from the multi-stage game. We develop an algorithm which enables the Twitter bot analyzer to automatically collect and analyze the data. The results from analyzing the data collected in our experiment show that the follow-back ratios for both of the Twitter bots are very low, which are 0.76%0.76%0.76% and 0.86%0.86%0.86%. This means that most of the Twitter users do not cooperate and only want to be followed instead of following others. Our results also exhibit the effect of different strategies on the follow-back followers and on the non-following followers as well.
Keywords: Decision theory; Game theoretic analysis; Game theory; Learning systems; Machine learning; Multi stage games; Social network; Social networking (online); Twitter bot; Twitter classification; Two-player games; dept.csc